Manejo del mal de hilachas (Pellicularia koleroga) en el cultivo de Café (Coffea arabica) - Liberio Miranda, Johnny David (2023)
One of the world's most important crops, coffee (Coffea arabica), has a significant economic impact, especially in developing countries. The most important disease affecting coffee-producing regions is lint disease (Pellicularia koleroga). The objectives were to describe the signs and effects of damage caused by the Pellicularia koleroga disease in the coffee crop (Coffea arabica), as well as the methods used to combat the disease. The findings show low productivity is generally due to lack of experience in crop management and lack of technology to find a solution. In terms of biotic issues, the disease is one in which the fungus initially develops on the underside of young branches and stems before the mycelium produces threads that pierce the cellular tissue. The life cycle of the fungus can last between 60 and 70 days and, depending on the climate, it usually appears when the plant is mature and during the months with more rainfall. On the stem and branches, the first symptoms are dark, rough threads. Which look like spider webs, these threads then extend to the leaves and adhere to them forming a white film. When the disease manifests itself for the first time, pruning, waste collection and burning are suggested as a control method to stop the spread of the disease and in addition, 100 liters of Bordeaux broth is suggested for each hectare of land, along with effective weed control measures.